2017
DOI: 10.1007/s40979-017-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Removing the opportunity for contract cheating in business capstones: a crime prevention case study

Abstract: Introduction: With a definition that is evolving, a serious component of the contract cheating issue involves individuals paying a third-party to complete assessment items for them and then submitting this work as if it were their own. The issue of contract cheating poses a significant problem for tertiary institutions. The research literature conducted to date has addressed contract cheating, yet few papers discuss theory-based prevention strategies, and even fewer still evaluate the impact of theory-based pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The results from this study may also be used to inform assessment design. Baird and Clare (2017) suggest that the opportunity structure for academic misconduct can be disrupted by implementing appropriate assessment designs. Bretag et al (2018b) have also been investigating how assessment design may influence student engagement in contract cheating.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study may also be used to inform assessment design. Baird and Clare (2017) suggest that the opportunity structure for academic misconduct can be disrupted by implementing appropriate assessment designs. Bretag et al (2018b) have also been investigating how assessment design may influence student engagement in contract cheating.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed extensively elsewhere in the literature on contract cheating (e.g. Mahmood, ; Baird & Clare, ; Clare et al ., ; Rogerson, ), this might include a stronger focus on timed and invigilated assessment techniques, varying assignments between classes (Baird & Clare, ), staged assessments and the use of a viva voce to support written work (Mahmood, ). These approaches are arguably less vulnerable to essay mill interference, as they require students to present themselves in person, or to engage in some form of interaction, to achieve the assessment outcome.…”
Section: Discussionmentioning
confidence: 94%
“…As indicated above, much prior work on contract cheating has focused on either the demand side, in terms of students’ willingness to pay for its outputs (Rigby et al ., ), or on the institutional perspective, with a particular focus on the detection and prevention of contract cheating by universities (Mahmood, ; Baird & Clare, ; Clare et al ., ; Rogerson, ). In terms of institutions militating against contract cheating, Baird and Claire () have suggested introducing a series of interventions into the design of student assessments. These include ( inter alia ) varying the basic group work assessment around different conditions, making it harder to share data between groups (an example of increasing the effort required to cheat) and making academic misconduct penalties more visible to students (an example of increasing perceived risk of contract cheating).…”
Section: Academic Misconduct and Integrity In He And Contract Cheatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Wellman and Fallon (2012) identified that contract cheating was taking place on an MBA level module. Baird and Clare (2017) found this occurring on a capstone project where students were working in interdisciplinary teams, but collaborating to agree to hire a third party. Both of these case studies could be considered as students outsourcing assessed work at a high academic level.…”
Section: Examples Of Contract Cheating Publications By Disciplinementioning
confidence: 99%